Modern art for kids : hands-on art and craft activities inspired by the masters - Ho Poon, Stephanie (Art Stars, 2023)
From Monet and Matisse to Van Gogh and Warhol, Modern Art for Kids is a guide to 20+ renowned artists, designed for both adults and children to enjoy together.